2016
DOI: 10.3389/fmicb.2016.02080
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of Type IV Pilin in Desulfuromonadales

Abstract: During anaerobic respiration, the bacteria Geobacter sulfurreducens can transfer electrons to extracellular electron accepters through its pilus. G. sulfurreducens pili have been reported to have metallic-like conductivity that is similar to doped organic semiconductors. To study the characteristics and origin of conductive pilin proteins found in the pilus structure, their genetic, structural, and phylogenetic properties were analyzed. The genetic relationships, and conserved structures and sequences that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…These relationships suggest that aromatic amino acids probably play a decisive role in the magnitude of conductivity. The three aromatic amino acids (F1, F24, and Y27) in each N-terminus of the WT and W51W57 pilin were arranged in a potential electrically conductive geometry in which they were sufficiently close (around 3.5 Å) to account for the experimentally observed metallic-like conductivity of the pili [3,14]. Therefore, the mechanism by which the G. sulfurreducens pilus transfers electrons along pili is attributed, at least in part, to the conjugation of aromatic amino acids (π-π interactions).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These relationships suggest that aromatic amino acids probably play a decisive role in the magnitude of conductivity. The three aromatic amino acids (F1, F24, and Y27) in each N-terminus of the WT and W51W57 pilin were arranged in a potential electrically conductive geometry in which they were sufficiently close (around 3.5 Å) to account for the experimentally observed metallic-like conductivity of the pili [3,14]. Therefore, the mechanism by which the G. sulfurreducens pilus transfers electrons along pili is attributed, at least in part, to the conjugation of aromatic amino acids (π-π interactions).…”
Section: Discussionmentioning
confidence: 99%
“…The conductivity of the Geobacter sulfurreducens pilus was increased by the genetic substitution of a tryptophan for each of the two aromatic amino acids (+51 tyrosines and +57 phenylalanines) in PilA (W51W57 mutant) [12], since tryptophan facilitates electron transport more effectively than tyrosines or phenylalanines [10,13]. Additionally, other studies also suggested that aromatic amino acids from different subunits were likely packed closely, resulting in π-π interactions that contribute to pili conductivity [3,8,14]. These results indicated that the mechanism for electron transfer in Geobacter has been attributed to the stacking of aromatic amino acids [3,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, unlike other T4a pilins, the gene encoding the precursor of the short pilins ( pilA‐N ) is organized in an operon with a gene ( pilA‐C ) coding for a hypothetical protein (Reguera et al ., 2005; Holmes et al ., 2016). The PilA‐C protein contains domains that could fold as antiparallel β‐sheets, a structural feature found in the globular head of canonical T4a pilins (Shu et al ., 2016). This has led to the suggestion that the genes encoding PilA‐N (pilin precursor) and PilA‐C (hypothetical protein) originated from the duplication of an ancestral full‐length pilin gene that lost the peptide's carboxyl‐ ( pilA‐N ) or amino‐ ( pilA‐C ) terminal regions (Shu et al ., 2016).…”
Section: Geobacter T4p: a Paradigm In Structure And Functionmentioning
confidence: 99%
“…The PilA‐C protein contains domains that could fold as antiparallel β‐sheets, a structural feature found in the globular head of canonical T4a pilins (Shu et al ., 2016). This has led to the suggestion that the genes encoding PilA‐N (pilin precursor) and PilA‐C (hypothetical protein) originated from the duplication of an ancestral full‐length pilin gene that lost the peptide's carboxyl‐ ( pilA‐N ) or amino‐ ( pilA‐C ) terminal regions (Shu et al ., 2016). The need to respire extracellular electron acceptors may indeed have exerted evolutionary pressure on an ancestral full‐length pilin to lose the more insulating β‐strands and acquire a predominantly α‐helical configuration for increased electronic coupling (Feliciano et al ., 2012).…”
Section: Geobacter T4p: a Paradigm In Structure And Functionmentioning
confidence: 99%